PARENTING PROGRAM TO IMPROVE QUALITY LEARNING IN INSTITUTIONS OF EARLY CHILDHOOD EDUCATION (CASE AT TK AT-TAUFIQIYAH AENGBAJARAJA BLUTO MADURA) - Thorik Aziz; Ria Astuti; Erni Munastiwi (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2018)
The success in the ECD program depends not only in the school managers, but also the family. It is important, therefore, to run a parenting program in integrating the perception of both school staffs and parents about the children. This paper aims to describe implementation of the program, an improving learning quality effort, and impact of the program on the learning quality in the Kingergarten At-Taufiqiyah, Bluto, Madura. This research indicates that the program works well in improving both learning quality and childrens‟ achievement mainly through the program of nurturing and guarding consisting of the physical-motorical, cognitive, moral-religiousity, emotional and social one. The improvement of learnig quality is performed through developing teachers capacity, providing sufficient learning facilities, enganging parents in the learning activity and understanding principles of early children learning. The principles are about learning activity by playing and singing, implementation of children development based learning, learning through life skill in interacting with others, learning from concrete thing and an integrated learning.